2017
DOI: 10.1186/s12864-017-3570-4
|View full text |Cite
|
Sign up to set email alerts
|

Leaf transcriptome analysis of a subtropical evergreen broadleaf plant, wild oil-tea camellia (Camellia oleifera), revealing candidate genes for cold acclimation

Abstract: BackgroundCold tolerance is a key determinant of the geographical distribution range of a plant species and crop production. Cold acclimation can enhance freezing-tolerance of plant species through a period of exposure to low nonfreezing temperatures. As a subtropical evergreen broadleaf plant, oil-tea camellia demonstrates a relatively strong tolerance to freezing temperatures. Moreover, wild oil-tea camellia is an essential genetic resource for the breeding of cultivated oil-tea camellia, one of the four maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Studies have revealed that extensive crosstalk exists among different hormonal signaling pathways, such as between JA and other hormonal signaling pathways, providing plants with a powerful regulatory potential against stresses (Pauwels et al 2009, Pieterse et al 2009. In this regard, Glyma.06G243500/JAR1, which acts as a positive regulator in JA-dependent induced systemic resistance (ISR) in plants (Chen et al 2017), was upregulated in the 'W+F vs W' comparison ( Fig. 6B).…”
Section: Crosstalk Among Hormones Plays Some Roles In the Differentiamentioning
confidence: 97%
“…Studies have revealed that extensive crosstalk exists among different hormonal signaling pathways, such as between JA and other hormonal signaling pathways, providing plants with a powerful regulatory potential against stresses (Pauwels et al 2009, Pieterse et al 2009. In this regard, Glyma.06G243500/JAR1, which acts as a positive regulator in JA-dependent induced systemic resistance (ISR) in plants (Chen et al 2017), was upregulated in the 'W+F vs W' comparison ( Fig. 6B).…”
Section: Crosstalk Among Hormones Plays Some Roles In the Differentiamentioning
confidence: 97%
“…To further investigate the proteins associated with fatty acid biosynthesis, which could serve as a foundation to understand the mechanisms of fatty-acid metabolism in oil crops [48], KEGG pathway analysis was carried out. As shown in the results, a total of 522 unigenes were involved in lipid metabolism, whereas just 17 special unigenes were translated into proteins.…”
Section: Annotation and Network Analyses Of Genes And Proteins Providmentioning
confidence: 99%
“…Tea oil has a similar chemical composition to that of olive oil; both contain high amounts of unsaturated fatty acids [4]. As an evergreen broadleaf shrub or small tree, C. oleifera is widely distributed in the subtropical mountainous areas of the Yangtze River basin and South China [5]. The Jiangxi, Hunan, and Guangxi provinces are the main habitat areas, accounting for 76% of the total area of production in the country [6].…”
Section: Introductionmentioning
confidence: 99%